Fibre-optic long period gratings with nano-structured overlays - Ishaq, I. M. (Cranfield University, 2006)
The influence of nano-structured overlays on the properties of fibre optic Long Period Gratings (LPGs) has been investigated. The presence of overlays of thickness of order 100 m is shown to significantly alter the response of the LPG to environmental parameters, such as the surrounding refractive index. A LPG with a nano-structured overlay was observed to exhibit enhanced sensitivity to refractive indices lower than silica, and was observed to exhibit sensitivity to refractive indices greater than that of the silica cladding, not observed in the absence of the overlay. A theoretical model predicts the observed behaviour. The observation was exploited to enhance the sensitivity of a LPG based chemical concentration sensor. The response of the transmission spectrum of concatenated long period gratings (LPGs) to ' the deposition of nano-structured overlays was also investigated. Concatenated LPGs act as a Mach-Zehnder interferometer and the phase of the interference fringes that appear within the LPGs° attenuation bands were shown to be highly sensitive to the optical thickness of the overlay, for thicknesses of order 100 mn. Several devices were fabricated with increasing path lengths to demonstrate effect of overlay thickness and refractive index on the transmission spectrum of the LPG.